Women entrepreneurs' digital social innovation: Linking gender, entrepreneurship, social innovation and information systems - Suseno, Yuliani; Abbott, Ling (Information Systems Journal, 2021)
This article responds to increasing discourses on digital social innovation (DSI) from the perspectives of women entrepreneurs. Using the individual differences theory of gender and information technology (IDTGIT), this research explores how digital technology is used by women entrepreneurs to create opportunities in response to the challenges associated with individual identity, individual influences, social influences and structural influences. We also extend the IDTGIT by exploring how technology is used by women entrepreneurs in their DSI ventures and how technology facilitates the social impact of such ventures. This paper draws on a qualitative study using interviews with 17 women entrepreneurs in Australia, and our findings indicate that individual identity, individual influences and social and structural influences play a significant role in inhibiting women entrepreneurs' business ventures but technology helps to create opportunities for women entrepreneurs to address these factors. We also found that technology plays a role in helping women entrepreneurs to pursue social innovation in two different ways: through social innovation that is embodied by technology and social innovation that is enabled by technology. Our findings further indicate the social impact of DSI in the areas of education, employment, environment and climate, community development and progress and healthcare. The theoretical and practical implications of DSI for women entrepreneurs are provided.
Number: 5
Keywords: Australie; Digital; Réservé UdeM